Деструкція гірничопромислових ландшафтів = The destruction of mining landscapes - Ivanov, Ievhen; Kovalchuk, Ivan (Journal of Education, Health and Sport, 2016)
Ivanov Ievhen, Kovalchuk Ivan. Деструкція гірничопромислових ландшафтів = The destruction of mining landscapes. Journal of Education, Health and Sport. 2016;6(5):369-392. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53161 http://ojs.ukw.edu.pl/index.php/johs/article/view/3530 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. Деструкція гірничопромислових ландшафтів The destruction of mining landscapes Євген Іванов, Іван Ковальчук Ievhen Ivanov, Ivan Kovalchuk Євген Іванов – кандидат географічних наук, доцент, докторант кафедри конструктивної географії і картографії Львівського національного університету імені Івана Франка. Іван Ковальчук – доктор географічних наук, професор, завідувач кафедри геодезії та картографії Національного університету біоресурсів і природокористування України. Eugen Ivanov – candidate of geographical science, docent, doctoral student of the Department of Constructive Geography and Cartography, Ivan Franko National University of L’viv. Ivan Kovalchuk – doctor of geographical science, professor, head of the Department of Geodesy and Cartography, National University of bioresources and nature use of Ukraine. Анотація. Розглянуто актуальні питання деструкції гірничопромислових ландшафтних систем. Акцентовано увагу на проблемах наукової термінології, зокрема на співвідношенні понять деструкції і деградації гірничопромислових геосистем. Охарактеризовано прояв деструктивних процесів та явищ в межах постмайнінгових ландшафтних систем. При цьому виявлено співвідношення і переважаючий напрямок основних видів міграційних потоків. Проаналізовано особливості зникнення і смерті кар’єрів, відвалів, відстійників, хвостосховищ та інших гірничопромислових територій та об’єктів. Існує три варіанти зникнення геосистем, які умовно називає розчиненням, перекриванням і заміщенням місця ландшафту. Про появу нових геосистем на місці гірничопромислових ландшафтів може свідчити зміна її господарського чи функціонального призначення. На основі аналізу деструктивних процесів та явищ, розглянуто варіанти ліквідації гірничовидобувних підприємств, запропоновано підходи щодо оптимізації постмайнінгових геосистем. Напрям оптимізаційних робіт (рекультивація чи ревіталізація) слід визначати для різних районів розроблення корисних копалин з урахуванням інтенсивності прояву деструктивних процесів та явищ, природно-географічних та соціально-економічних умов регіону. Ключові слова: деструкція, деградація, гірничопромислова ландшафт, постмайнінговий ландшафт, ревіталізація, оптимізація. Abstract. In the article considered actual questions of mining landscape systems destruction. Accented attention on problems of scientific terminology, in particular on interrelation of destruction and degradation of mining geosystems definitions. Also, characterize display of destructive processes and phenomena within post-mining landscape systems. After research found interrelation and dominant direction of migration flows main kinds. Analyzed features of quarries dumps, septic tanks, tailings and other mining areas and objects disappearance and death. Exist three variants of geosystems disappearance conventionally called dissolution, overlap and substitution of landscape place. The appearance of new geosystems on-site mining landscapes may indicate a change of the economic or functional purposes. Based on analysis of destructive processes and phenomena discussed options for liquidation of mining companies, suggested approaches for optimizing post-mining geosystems. Direction of optimization works (recultivation or revitalization) should be defining for different mineral resources development areas on basis of display intensity of destructive processes and phenomena, natural geographic and socio-economic conditions of the region. Key words: destruction, degradation, mining landscape, post-mining landscape, revitalization, optimization.